P-127 E-TEP ASSISTED REVERSE-TAR FOR THE TREATMENT OF LARGE LUMBAR INCISIONAL HERNIAS ASSOCIATED TO MIDLINE DEFECTS. (13th October 2022) - Lopez-Monclus, J; Roman Garcia De Leon, L; Muñoz Rodriguez, J; Blazquez Hernando, L; Robin, A; Polaino Moreno, V; Rial Justo, X; Lucena De La Poza, J L; Iglesias Garcia, E; Garcia Ureña, M A
Abstract: Aim: To describe a new hybrid surgical approach of large lumbar incisional hernias (IH) associated to synchronic midline defects. Material and Methods: Prospective multicentric study including patients with large lumbar hernias (L4W3) associated to midline abdominal wall defects. Surgical intervention starts with a bilateral retrorectus dissection performed through a minimally invasive extraperitoneal endoscopic approach (eTEP). Once this space has been dissected, the lumbar IH is treated with an overextended centrifugal preperitoneal open approach through the previous lumbar incision. Afterwards the dissected spaces are communicated performing a reverse transversus abdominis release (TAR) from lateral to medial. A prosthetic preperitoneal repair is performed with an absorbable and permantent meshes that cover the space dissected. Results: Five patients were included in the study. All patients had lumbar hernias L4W3 associated to primary or incisional midline hernias M1–5 W1–2. Eighty percent of the patients were women, with a mean age of 62 years. Mean BMI was 32 (range 30–34), with a 60% of diabetic patients, and 80% of recurrent lumbar hernias (between 1 and 3 previous repair attempts). Mean surgical time was 198 minutes (range 160–250). Mean hospital stay was 5 days (range 4–8 days). Two lumbar hematomas which didn't required any interventional procedure took place as the only surgical site occurrences, without any systemic complications. No recurrence has taken place after 5 months mean follow up (range 2–9 months) Conclusion: Hybrid eTEP and open approach of large lumbar hernias associated with small midline defects seem to be an efficient and safe approach.